2013
DOI: 10.1155/2013/638312
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Cortex Reorganization in Alzheimer's Disease and Metal Dysfunction: A MEG Study

Abstract: Objective. To verify whether systemic biometals dysfunctions affect neurotransmission in living Alzheimer's disease (AD) patients. Methods. We performed a case-control study using magnetoencephalography to detect sensorimotor fields of AD patients, at rest and during median nerve stimulation. We analyzed position and amount of neurons synchronously activated by the stimulation in both hemispheres to investigate the capability of the primary somatosensory cortex to reorganize its circuitry disrupted by the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The present work is pioneering the investigation of spinal cord alterations in patients with dementia, and in particular with AD, a major neurodegenerative disease known for its profound effects on cognitive functions. The motor/sensorimotor system has already been shown to be affected in AD at various levels in the brain, but nobody has yet investigated the spinal cord (Agosta et al, 2010;Salustri et al, 2013;Castellazzi et al, 2014;Albers et al, 2015;Fu et al, 2018). Here, we have shown that the spinal cord is significantly atrophic in established AD patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The present work is pioneering the investigation of spinal cord alterations in patients with dementia, and in particular with AD, a major neurodegenerative disease known for its profound effects on cognitive functions. The motor/sensorimotor system has already been shown to be affected in AD at various levels in the brain, but nobody has yet investigated the spinal cord (Agosta et al, 2010;Salustri et al, 2013;Castellazzi et al, 2014;Albers et al, 2015;Fu et al, 2018). Here, we have shown that the spinal cord is significantly atrophic in established AD patients.…”
Section: Discussionmentioning
confidence: 63%
“…As the spinal cord is relaying sensorimotor control signals from the cortex to the peripheral nervous system and vice versa, it is indeed important to assess whether it is affected by atrophy in a disease that is known for its involvement of cognitive domains. Recent indications suggest that there is definitely a sensorimotor network rewiring and that the motor system may even be affected before cognitive functions in AD (Agosta et al, 2010;Salustri et al, 2013;Castellazzi et al, 2014;Albers et al, 2015;Fu et al, 2018). Clinical symptoms of early AD include, amongst others, fine motor impairment, with for example worsening of writing abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the control group, both the MCI and AD disease groups demonstrated weaker positive connectivity within the auditory and sensorimotor networks and also weaker positive connections between these two networks. Some previous studies have found altered activity and connectivity in these two networks that are related to the Alzheimer disease (Agosta et al, 2010; Goll et al 2012; Salustri et al 2013; Terranova et al 2013; Ferreri et al 2016). …”
Section: Resultsmentioning
confidence: 96%
“…It is tempting to speculate that, as the more susceptible areas of the brain are affected in early dementia, the more resistant areas such as the sensorimotor cortex may provide cognitive reserve and higher neuronal activity following lifestyle interventions. 73 …”
Section: Discussionmentioning
confidence: 99%